The Future of the Witness: Nature, Race and More-than-Human Environmental Publics - SHEIKH, SHELA (Kronos: Southern African Histories, 2020)
In a 2014 article entitled ‘Ecology, Race, and the Making of Environmental Publics: A Dialogue with Silent Spring in South Africa’, anthropologist Lesley Green identifies obstacles to the creation of an ‘environmental public’ in contemporary post-apartheid South Africa.1 The broader backdrop against which Green writes – one that is experienced globally to differing degrees and often in distinct manners – is that of environmental violence that is enacted both against racialised human bodies and against nature, and, with this, the entanglement between abuses of human and nonhuman rights. For a start, violations of human rights, in South Africa and beyond, have been and often continue to be carried out through the natural environment, using scorched-earth tactics, environmental remodelling, industrial-scale agriculture, the creation of enclosures,2 dispossession through land-grabbing, and so on. Moreover, in the context of ‘environmental racism’, such violations are often enacted against racialised populations who are rendered culturally and politically ‘disposable’ or ‘sacrificeable’. Included here are climate refugees or, in the case of contemporary South Africa, those denied access to potable water, exposed to higher levels of pollution and/or toxicity, or removed from their land to enhance the profitability of extractive capitalism – such as mining – or, more sinisterly, removed from their land in the name of conservation.